Prediction of crude protein digestibility of animal by-product meals for dogs by the protein solubility in pepsin method - Kawauchi, Iris M. [UNESP]; Sakomura, Nilva K. [UNESP]; Pontieri, Cristiana F. F.; Rebelato, Aline [UNESP]; Putarov, Thaila C. [UNESP]; Malheiros, Euclides B. [UNESP]; Gomes, Márcia de O. S. [UNESP]; Castrillo, Carlos; Carciofi, Aulus C. [UNESP] (Journal of Nutritional Science, 2014)
Animal by-product meals have large variability in crude protein (CP) content and digestibility. In vivo digestibility procedures are precise but laborious, and in vitro methods could be an alternative to evaluate and classify these ingredients. The present study reports prediction equations to estimate the CP digestibility of meat and bone meal (MBM) and poultry by-product meal (PM) using the protein solubility in pepsin method (PSP). Total tract CP digestibility of eight MBM and eight PM samples was determined in dogs by the substitution method. A basal diet was formulated for dog maintenance, and sixteen diets were produced by mixing 70 % of the basal diet and 30 % of each tested meal. Six dogs per diet were used to determine ingredient digestibility. In addition, PSP of the MBM and PM samples was determined using three pepsin concentrations: 0·02, 0·002 and 0·0002 %. The CP content of MBM and PM ranged from 39 to 46 % and 57 to 69 %, respectively, and their mean CP digestibility by dogs was 76 (2·4) and 85 (2·6) %, respectively. The pepsin concentration with higher Pearson correlation coefficients with the in vivo results were 0·0002 % for MBM (r 0·380; P = 0·008) and 0·02 % for PM (r 0·482; P = 0·005). The relationship between the in vivo and in vitro results was better explained by the following equations: CP digestibility of MBM = 61·7 + 0·2644 × PSP at 0·0002 % (P = 0·008; R (2) 0·126); and CP digestibility of PM = 54·1 + 0·3833 × PSP at 0·02 % (P = 0·005; R (2) 0·216). Although significant, the coefficients of determination were low, indicating that the models were weak and need to be used with caution.
Keywords: Cp, crude protein; Dog food; In vitro methods; Mbm, meat and bone meal; Meat and bone meal; Pm, poultry by-product meal; Psp, protein solubility in pepsin; Poultry by-product meal